The Human Skin Microbiome in Selected Cutaneous Diseases - Carmona-Cruz, Silvia; Orozco-Covarrubias, Luz; Sáez-de-Ocariz, Marimar (Frontiers in Cellular and Infection Microbiology, 2022)
The human skin is colonized by variety of microorganisms which, together with their genomes and interactions with the host, constitute the human skin microbiome. In recent years, interest in the role of the human microbiome in the development of different diseases has grown, and the field of dermatology is no exception. Different studies have shown that modifications in the cutaneous microbiome play a role in the pathogenesis of different skin diseases. A better characterization of the human microbiome and its interaction with the immune system may allow deeper understanding of these pathologies, and even the opportunity to create new therapeutic modalities. This review focuses on the most recent knowledge on skin microbiome and its participation in pathophysiology of several skin disorders: alopecia areata, seborrheic dermatitis, alopecia areata, psoriasis and acne.